2021
DOI: 10.3390/microorganisms9081751
|View full text |Cite
|
Sign up to set email alerts
|

First Genome Description of Providencia vermicola Isolate Bearing NDM-1 from Blood Culture

Abstract: In this paper, we describe the first complete genome sequence of Providencia vermicola species, a clinical multidrug-resistant strain harboring the New Delhi Metallo-β-lactamase-1 (NDM-1) gene, isolated at the Kinshasa University Teaching Hospital, in Democratic Republic of the Congo. Whole genome sequencing of an imipenem-resistant clinical Gram-negative P. vermicola P8538 isolate was performed using MiSeq and Gridion, and then complete genome analysis, plasmid search, resistome analysis, and comparative geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
(36 reference statements)
1
4
0
Order By: Relevance
“…Our results are further supported by the fact that genome comparison of both P. vermicola and P. stuartii revealed a proteome similarity of 90.79%. 53 Similar evidence was also observed in another work where P. vermicola type strain in a clade showed 100 bootstrap support in the strains of both the species P. stuartii and P. thailandensis. 28…”
supporting
confidence: 82%
See 1 more Smart Citation
“…Our results are further supported by the fact that genome comparison of both P. vermicola and P. stuartii revealed a proteome similarity of 90.79%. 53 Similar evidence was also observed in another work where P. vermicola type strain in a clade showed 100 bootstrap support in the strains of both the species P. stuartii and P. thailandensis. 28…”
supporting
confidence: 82%
“…In a more recent study, it was found that P. vermicola also exhibits multi-drug resistance, which is a cause of major concern in terms of clinical significance. 53 The lowest concentration or the MIC for moL12 is 10 mg/mL (as shown in Figure 2).…”
Section: Minimum Inhibitory Concentrationmentioning
confidence: 99%
“… Providencia stuartii infections are difficult to manage ( 3 ) and are often resistant to multiple antibiotics ( 7 9 ). The NDM-1 carbapenemase gene has been detected in Providencia vermicola isolates ( 10 , 11 ).…”
Section: Announcementmentioning
confidence: 99%
“…The species Providencia vermicola P8438 was found to be the closest relative to isolate M7 and has multiple Mobile Genetic Elements (MGEs) genes, DNA segments that encode enzymes, and other proteins that facilitate the movement of genetic material between bacterial chromosomes. On the P. vermicola chromosome P8438, a Nonribosomal Peptide Synthase (NRPS) cluster was also found which functions for siderophore biosynthesis (Lupande-Mwenebitu et al, 2021). The genus Providencia spp.…”
Section: Colony Characteristics and Siderophores Productionmentioning
confidence: 99%